Dpal Rdo-rje-sems-dpaʼ thugs kyi sgrub paʼi bsñen sgrub phrin las kyi cho ga rnam grol lam bzaṅ źes bya ba bźugs so - Gter-bdag-gliṅ-pa ʼGyur-med-rdo-rje, 1646-1714 (s.n., 1970)
Esoteric Buddhist ritual from the liturgy of Mindoling Monastery and its affiliates.